The figurations of the subject "people" in the African Charter on Human and Peoples' Rights : a contextualist examination of a collective subjectivity - (:unkn) unknown (My University, 2022)
The intrinsic indeterminacy of the notion of “people” combined with the normative scope of the subjectification of this collective entity in the African Charter on Human and Peoples’ Rights necessarily calls for the formulation of a question: what is the subject “people” in the Nairobi Charter? More precisely, what are the figurations of this subject proposed by the different actors of African human rights law? The ambition of this thesis is to decipher the meaning and content of this subjectivity, both in terms of the actors who have used it and the socio-historical moments in which it was mobilised. A contextualist analysis that pays attention to the relationship between the law and its historical, political and social environment allows us to distinguish between two different representations. One, decolonial, carried by the drafters of the Charter, identifies the subject “people” with the collectivity constituted by the colonial territory and recognises its right to become independent and to constitute itself as a state within the limits of this territoriality. The other, post-colonial, supported by the interpreters of the Charter, identifies the subject “people” with non-state collectivities, with forms of identity and allegiance disjunctive to those of the state-national collectivity, and recognises their right to autonomy (political, legal, linguistic) respectful of the sovereignty of the states that encompass them. These two representations coexist and are complementary because they do not address the same collective entities. In different temporalities and according to divergent stakes, they have both participated in the enrichment of the protection of human rights on the African continent.
Keywords: African Research